Improving Identification and Child-Focused Collaborative Care for Children of Parents With a Mental Illness in Tyrol, Austria - Christiansen, Hanna; Bauer, Annette; Fatima, Batool; Goodyear, Melinda; Lund, Ingunn Olea; Zechmeister-Koss, Ingrid; Paul, Jean Lillian (Frontiers in Psychiatry, 2019)
Background: Children of parents with a mental illness (COPMI) are more likely to experience negative long-term adversities, however interventions to support their needs early can significantly enhance adjustment and reduce negative outcomes. Approximately one in four children currently lives with a parent with mental illness worldwide. The lifelong impact for individuals, governments and wider society is likely to be substantial. There are significant workforce barriers to the early identification of COPMI and addressing their needs, particularly within the adult mental health care system. Objectives: The project “The Village” seeks to improve child development and wellbeing outcomes for children of parents with a diagnosed mental illness. This will be achieved through the co-development, implementation and evaluation of a practice approach to the early identification and collaborative care for COPMI, through establishing child-focused support networks. This will be done with open innovation science (OIS) approaches engaging the public in Tyrol, a geographical region of Austria, over the period of four years. Methods: The project is underpinned by theories from implementation science, symbolic interactionism, and realist evaluation. It will be carried out through content work packages to scope, co-design, implement and evaluate the practice approaches. “Scoping” will involve exploring the existing evidence, practice, and current state of identification and collaborative care in Austria. “Co-design” will involve the set-up of practice approaches to identify and support children in partnership with key stakeholders and service providers working in Tyrol. The “implementation” of practice approaches will be based on support strategies that draw on known organisational drivers and infrastructure support mechanisms from the field of implementation science. “Evaluation” will involve: formative, process, (cost-)effectiveness, and impact evaluations and will follow a realist approach. The “dissemination” step will continuously focus on reaching a broad public audience of different stakeholders, researchers, and families involved. Discussion: The research project aims to directly improve identification and support of vulnerable children across selected regions in Tyrol, Austria, and by doing so, improve the health and wellbeing of future generations, through breaking the cycle of intergenerational transfer of adverse childhood experiences.